2017 IEEE 3rd International Conference on Collaboration and Internet Computing (CIC) 2017
DOI: 10.1109/cic.2017.00036
|View full text |Cite
|
Sign up to set email alerts
|

dTrust: A Simple Deep Learning Approach for Social Recommendation

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Also, privacy is one of the issues in social recommender systems as these systems rely on user personal details. To address this problem, Dang et al [66] propose a rating prediction approach called "dTrust" that exploits the topology of trust-user-item network. This approach uses deep feedforward neural network to combine user relations and user-item ratings to predict ratings.…”
Section: Miscellaneousmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, privacy is one of the issues in social recommender systems as these systems rely on user personal details. To address this problem, Dang et al [66] propose a rating prediction approach called "dTrust" that exploits the topology of trust-user-item network. This approach uses deep feedforward neural network to combine user relations and user-item ratings to predict ratings.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Moreover, deep learning has also opened the doors for improving the accuracy of social recommender systems. [19], [37], [44], [46], [52] 2016 17 [16], [21], [24], [25], [28], [36], [40], [41], [45], [47], [57], [60], [61], [69], [70], [65], [71] 2017 20 [17], [18], [20], [22], [26], [27], [38], [42], [43], [51], [53], [62]- [64], [66], [68], [72]- [74], [78] VI. CONCLUSION A voluminous research has been done and is also proceeding in recommender systems using deep learning.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Deep learning for recommender systems becomes popular research topic in 2016 during ACM RecSys . The reasons for integrating deep learning with recommender systems are the ability of deep learning to build complex non linear relationship in input and output data, better scalability for large scale of data and better analysing incorrect label data [15]. Researchers have observed that integrating these techniques improves recommendation in tremendous manner.…”
Section: Deep Learning Based Recommendationmentioning
confidence: 99%
“…Multilayer perceptron can be applied on user-item ratings to improve recommender systems. It is the simplest model [14] .It can approximate any function [15]. The advantage of using this model is that data need not be input separately as it is directly be used in multilayer neural network model.…”
Section: Deep Learning Based Recommendationmentioning
confidence: 99%
“…In most popular signed directed social networks, the signs of links represent trust (positive) or distrust (negative) relationships between users [6]. Studies [7], [8] showed that trust relations play an important role in predicting user behaviors in e-commerce.…”
Section: Introductionmentioning
confidence: 99%